Phosphoinositide 3-Kinase Signaling in the Tumor Microenvironment: What Do We Need to Consider When Treating Chronic Lymphocytic Leukemia With PI3K Inhibitors? - Aydin, Ebru; Faehling, Sebastian; Saleh, Mariam; Llaó Cid, Laura; Seiffert, Martina; Roessner, Philipp M. (Frontiers in Immunology, 2021)
Phosphoinositide 3-kinases (PI3Ks) and their downstream proteins constitute a signaling pathway that is involved in both normal cell growth and malignant transformation of cells. Under physiological conditions, PI3K signaling regulates various cellular functions such as apoptosis, survival, proliferation, and growth, depending on the extracellular signals. A deterioration of these extracellular signals caused by mutational damage in oncogenes or growth factor receptors may result in hyperactivation of this signaling cascade, which is recognized as a hallmark of cancer. Although higher activation of PI3K pathway is common in many types of cancer, it has been therapeutically targeted for the first time in chronic lymphocytic leukemia (CLL), demonstrating its significance in B-cell receptor (BCR) signaling and malignant B-cell expansion. The biological activity of the PI3K pathway is not only limited to cancer cells but is also crucial for many components of the tumor microenvironment, as PI3K signaling regulates cytokine responses, and ensures the development and function of immune cells. Therefore, the success or failure of the PI3K inhibition is strongly related to microenvironmental stimuli. In this review, we outline the impacts of PI3K inhibition on the tumor microenvironment with a specific focus on CLL. Acknowledging the effects of PI3K inhibitor-based therapies on the tumor microenvironment in CLL can serve as a rationale for improved drug development, explain treatment-associated adverse events, and suggest novel combinatory treatment strategies in CLL.